2003
DOI: 10.1002/chin.200338255
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic Anion Sensors

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Recent studies have shown that fluorescent sensors for anions attracted a great deal of interest because of foundational roles of anions in chemical and biological processes [1][2][3][4][5][6][7][8][9][10]. Among these anions, fluoride ions (F − ) are one of the most attractive objects due to their great significance for health and environmental problems such as osteoporosis treatment, dental care and water supply treatment [11][12][13][14][15][16][17][18]. However, excess fluoride exposure might cause fluorosis and urolithiasis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that fluorescent sensors for anions attracted a great deal of interest because of foundational roles of anions in chemical and biological processes [1][2][3][4][5][6][7][8][9][10]. Among these anions, fluoride ions (F − ) are one of the most attractive objects due to their great significance for health and environmental problems such as osteoporosis treatment, dental care and water supply treatment [11][12][13][14][15][16][17][18]. However, excess fluoride exposure might cause fluorosis and urolithiasis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of receptors to recognize, sense and bind the anions is an important area of supramolecular chemistry [1][2][3][4][5]. Calix [4]pyrroles are conformationally flexible macrocycles [6,7] of significant importance due to their binding under different conditions with anions [8], neutral substrates [9] and metal ions [10].…”
Section: Introductionmentioning
confidence: 99%
“…The recognition and sensing of anions has emerged recently as a key research area within the generalized area of Journal of Quantum Chemistry [1][2][3][4][5][6][7][8]. In this study, optimization was carried at DFT level, while electronic absorption spectra were computed as vertical electronic excitations from the ground state using TD-DFT approach.…”
Section: Discussionmentioning
confidence: 99%
“…Among the entire applicability domain, the recognition and sensing of anions is one of the recently emerged and challenging areas in the field of research. This is due to the important role played by anions in the field of biological, industrial, agricultural, and environmental processes [1][2][3][4][5][6][7][8]. This importance can be visualized from the facts that majority of enzymes bind anions as either substrate or cofactor and many act as ubiquitous nucleophiles, bases, redox agents, and phase transfer catalysts [9,10].…”
Section: Introductionmentioning
confidence: 99%